Clinical value of serum SIRT1 combined with uterine hemodynamics in predicting disease severity and fetal growth restriction in preeclampsia - Kong, JianYing; Ge, TongJun (Journal of Medical Biochemistry, 2023)
Objective To investigate the effect and correlation of serum SIRT1 combined with uterine hemodynamic parameters on disease severity and fetal uterine growth restriction in the progression of preeclampsia, and to evaluate its clinical value as potential markers. Methods A total of 100 patients with preeclampsia who were hospitalized in Qufu Normal University Hospital from June 2017 to June 2021 were selected as the research objects. According to the severity, they were divided into Mild group (62 cases) and Severe group (38 cases), and according to whether the fetal growth restriction was combined or not, they were divided into the Combined fetal growth restriction group (56 cases) and the Uncomplicated fetal growth restriction group (44 cases). Serum SIRT1 expression and uterine artery hemodynamic parameters were detected, and spearman analysis was used to evaluate the association of serum SIRT1 expression and uterine artery hemodynamic parameters (peak-to-trough ratio of arterial blood velocity, pulsatility index, resistance index) with disease severity (systolic blood pressure, diastolic blood pressure, and random urinary protein levels) and fetal growth restriction (femoral length, biparietal diameter, head circumference and neonatal weight); unsupervised PCA analysis, supervised PLS-DA analysis, Cluster heat map analysis, ROC curve and AUC analysis were used to evaluate the diagnostic value of serum SIRT1 expression combined with uterine artery hemodynamic parameters in the severity of disease and fetal growth restriction in patients with preeclampsia. Results Serum SIRT1 expression was decreased in patients with severe preeclampsia (p < 0.0001), arterial blood flow velocity peak-to-trough ratio, pulsatility index and resistance index were increased (p < 0.001; p < 0.0001), and serum SIRT1 expression and uterine artery hemodynamic parameters were closely related to disease severity (p < 0.001; p < 0.0001). In addition, the expression of serum SIRT1 in patients with preeclampsia combined with fetal growth restriction was decreased (p < 0.0001), the peak-to-trough ratio of arterial blood flow velocity, pulsatility index and resistance index were increased (p < 0.0001), and serum SIRT1 expression and uterine artery hemodynamics were closely related to fetal growth restriction (p < 0.0001). Unsupervised PCA analysis and supervised PLS-DA analysis showed that patients with different severity of disease and patients with or without fetal growth restriction were similar within groups, and there were significant differences between groups; cluster heat map analysis showed that mild and severe groups were stratified clustering, the combined fetal growth restriction group and the uncombined group were hierarchically clustered; ROC curve and AUC analysis showed that serum SIRT1 expression combined with uterine artery hemodynamic parameters had a significant effect on the severity of preeclampsia and whether combined with fetal growth restriction. high diagnostic value. Conclusion Serum SIRT1 combined with uterine hemodynamic parameters in preeclampsia is closely related to disease severity and fetal growth restriction, and is expected to become potential biomarkers for early clinical intervention in patients.